Pengaruh Brand Ambassador Babe Cabita dan Marshel Widianto terhadap Brand Image Ms Glow for Men - Tania Dewi Priscilia; Rezha Pratama Putra; Nadya Chendana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The major goal of this study is to investigate the impact that MS Glow for Men brand ambassadors Marshel Widianto and Babe Cabita have on the company's reputation. Utilizing a rigorous technique, data is methodically gathered via an online survey distribution sent on Instagram with all of the @msglowformen Instagram profile's followers. Purposive sampling is used to properly choose the 400 respondents that make up the sample of the study. The output uncovered a substantial and remarkable effect attributed to Babe Cabita and Marshel Widianto in shaping the brand image perception of MS Glow for Men. The variable (X) of brand ambassador emerges as a pivotal element, elucidating a substantial portion, roughly amounting to 65.1%, of the observed variations in the brand image variable (Y). This formidable influence, as convincingly demonstrated by a robust regression coefficient of 0.551, unequivocally underscores the paramount importance and profound significance of this research endeavor in the realm of marketing and brand management.